Primary pulmonary hepatoid carcinoma: Report of a case and review of the literature. Issue 9 (6th April 2013) - Lin, Shiou‐Fu; Hsu, Wen‐Hu; Chou, Teh‐Ying
Abstract: Hepatoid carcinoma is a rare malignancy defined as extrahepatic primary alpha‐fetoprotein‐producing carcinoma morphologically resembling hepatocellular carcinoma. It is extremely rare in the lungs, with ambiguous pathological descriptions and variable prognosis. Herein, we present the case of a 66‐year‐old man with a primary pulmonary hepatoid carcinoma in his right upper lung who received complete curative surgical resection and adjuvant chemotherapy. No signs of recurrence or distant metastasis have been observed for 57 months postoperation. In addition, the literature is reviewed and the pathological diagnostic pitfalls are discussed.